2007
DOI: 10.1007/s12043-007-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-induced parametric dispersion and amplification in doped semiconductor plasmas

Abstract: Using the hydrodynamic model of semiconductor plasma, the diffusioninduced nonlinear current density and the consequent second-order effective susceptibility are obtained under off-resonant laser irradiation. The analysis deals with the qualitative behaviour of the anomalous parametric dispersion and the gain profile with respect to the excess doping concentration and pump electric field. The analysis suggests that a proper selection of doping level and pump field may lead to either positive or negative enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In quantum semiconductor devices, it is substantial to investigate the impacts of quantum mechanics on the behavior of charge carriers to work with electrons and holes at the nanometer-sized semiconductors [10]. Semiconductors are used in many complexes, fast, and sensitive electronic devices because of their compactness, relaxation time management, and highly advanced manufacturing technology [11]. In the new miniature semiconductors, de Broglie wavelengths of charge carriers are comparable to system scales such as Debye shielding length, so quantum effects are very important.…”
Section: Introductionmentioning
confidence: 99%
“…In quantum semiconductor devices, it is substantial to investigate the impacts of quantum mechanics on the behavior of charge carriers to work with electrons and holes at the nanometer-sized semiconductors [10]. Semiconductors are used in many complexes, fast, and sensitive electronic devices because of their compactness, relaxation time management, and highly advanced manufacturing technology [11]. In the new miniature semiconductors, de Broglie wavelengths of charge carriers are comparable to system scales such as Debye shielding length, so quantum effects are very important.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear parametric (NLP) interactions in semiconducting materials have been studied by a number of researchers. [1][2][3][4][5][6][7][8] These interactions provide useful information regarding the physical properties of the host medium. A variety of nonlinear effects have been observed in the interaction of high-power electromagnetic waves with semiconductor plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…real as a function of k at a particular pump electric field E 0 in the vicinity of the threshold |E 0th |. It can be observed that χ(3) …”
mentioning
confidence: 97%